2023
DOI: 10.1111/1759-7714.15182
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐related exosomal circ_0001715 promotes lung adenocarcinoma cell proliferation and metastasis via enhancing M2 macrophage polarization by regulating triggering receptor expressed on myeloid cells‐2

Mengjun Chen,
Chengzhang Cao,
Jun Ma

Abstract: BackgroundCircular RNAs (circRNAs) have been shown to mediate tumor‐associated macrophages (TAMs) to regulate the development of many cancers, including lung adenocarcinoma (LUAD). However, whether circ_0001715 regulates LUAD progression by mediating TAMs polarization remains uncertain.MethodsMonocytes (THP‐1) were treated with PMA to induce M0 macrophages. M0 macrophages were incubated with LUAD cells‐derived exosomes and then cocultured with LUAD cells. The levels of circ_0001715, M2 macrophage markers, micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…However, our findings only indicated a positive correlation of NGEF expression with M 0 macrophage. Another study shows that knockdown of Circ_0001715 in M 0 macrophages suppresses LUAD cell proliferation, migration and invasion [ 62 ]. Thus, M 0 macrophages may play important role in cancer cell proliferation, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings only indicated a positive correlation of NGEF expression with M 0 macrophage. Another study shows that knockdown of Circ_0001715 in M 0 macrophages suppresses LUAD cell proliferation, migration and invasion [ 62 ]. Thus, M 0 macrophages may play important role in cancer cell proliferation, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…The examination’s primary focus is the CTC count, with a positive threshold of ≥ 5, typically representing a poor prognosis. The persistence of CTC following therapy is associated with a poorer prognosis, and studies have demonstrated that changes in the quantity of CTC provide better predictive information than baseline CTC status ( 76 , 77 ). The number of CTCs present before beginning neoadjuvant therapy hurts survival, according to a meta-analysis of 2239 breast cancer patients from 21 trials (246) ( 60 ).…”
Section: Importtant Areas Of Clinical Applications Of Ctcs、ctdna and Evsmentioning
confidence: 99%
“… 15 Circ0001715 sponges miR-205-5p to enhance TREM2 expression, which in turn promotes M2 macrophage polarization and lung adenocarcinoma cell proliferation and metastasis. 16 Additionally, hypoxia-induced exosomal circPLEKHM1 serves as a prognostic biomarker for patients with non-small cell lung cancer and facilitates macrophage polarization and tumor metastasis. 17 In recent years, an increasing number of studies have shown that circRNAs play an important role in the metastatic mechanisms of melanoma.…”
Section: Introductionmentioning
confidence: 99%